Lexical Cohesion Analysis On Scopus Indexed-Journal Entitled “A New Control Method For Power Based On Dynamic Evolution Control “ - Sri Wahyono; Nur Hasyim; Ade Sukma Mulya (Epigram, 2020)
Cohesion is a semantic concept and part of the system of a language. The language can be orally or written. One of the indicators of good discourse (written) is having good cohesion and coherence aspect. This study is entitled Lexical Cohesion Analysis on Scopus-Indexed-Journal entitled “A New Control Method for Power based on Dynamic Evolution Control“. The aim of this study is to identify and describe the lexical cohesion in the Scopus-indexed article journal. This study is a qualitative research. The data sources in this study an article Scopus indexed-journal was obtained by purposive sampling. Furthermore, analysis of the data was done by identifying and classifying the data that related to cohesion, based on the theory of Halliday and Hasan (1976) and also analyzing used Spradley (1980). Based on the analysis, it was found five things related to cohesion and coherence. First, lexical cohesion devices which are used consist of repetition, synonymy, antonymy, hyponymy, and meronymy. The most frequent lexical cohesion used is repetition. Therefore, it can be of an interest to the (future) writer or researcher who are involved in writing journal. The study concludes that lexical cohesion determines writers’ tones in writing article and this ultimately contributes significantly enough in constructing persuasion and strong desire to persuade editorial boards of the journal to accept the article. It has also been highlighted that the findings of this study could be broaden in grammatical cohesion, and also be beneficial to researchers and ESL/EFL learners especially in persuasive and academic writing. Those aspects and factors can be considered to certain paper or journal article whether rejected or accepted in Scopus-indexed journal.